Cluster analysis of Model for End-stage Liver Disease and European System for Cardiac Operative Risk Evaluation for predicting operative mortality after concomitant tricuspid valve surgeryCentral MessagePerspective - Kevin Lim, FRCS (Ed); Antony Chin Ching Au, MB ChB; Matthew Ming Hon Hui, MRCS (Ed); Ivan Chi Hin Siu, MRCS (Ed); Simon Chi Ying Chow, FRCS (Ed); Jacky Yan Kit Ho, FRCS (Ed); Song Wan, FRCS (Ed), FACC; Randolph Hung Leung Wong, FRCS (Ed) (JTCVS Structural and Endovascular)
Objective: Patients requiring concomitant tricuspid surgery represent a heterogeneous cohort with significant comorbidities and varying degrees of organ and right ventricular dysfunction. However, surgeons can rely on little beyond intuition and experience when discussing operative risks. The objective of the study is to assess how the Model for End-stage Liver Disease score complements the European System for Cardiac Operative Risk Evaluation II in risk assessment. Methods: We performed a single-center retrospective cohort study of 369 consecutive patients who underwent concomitant tricuspid valve surgery from 2011 to 2020. Multivariate analysis of factors affecting operative mortality was performed, producing 2 multivariate risk prediction models, one consisting of European System for Cardiac Operative Risk Evaluation II components and the other consisting of both European System for Cardiac Operative Risk Evaluation II components and Model for End-stage Liver Disease. The models were compared by measuring c-statistic using the Hanley-McNeil method. This was further evaluated with category-free net reclassification improvement index. K-means clustering was performed using Model for End-stage Liver Disease and European System for Cardiac Operative Risk Evaluation II values after scalar transformation as independent variables and operative mortality as the dependent variable. Results: The Model for End-stage Liver Disease is an independent predictor of operative mortality, with an adjusted odds ratio of 1.286 per point. Inclusion of the Model for End-stage Liver Disease improves the discriminatory power of the European System for Cardiac Operative Risk Evaluation II for operative mortality, with a difference in area under the curve of 0.128 [0.0341-0.222] (P = .0076). The net reclassification improvement index of incorporating Model for End-stage Liver Disease with European System for Cardiac Operative Risk Evaluation II was 0.959 [0.515-1.392], indicating significant improvement in risk reclassification. Cluster analysis identified a unique cohort of patients with intermediate-to-high Model for End-stage Liver Disease, not previously identified with European System for Cardiac Operative Risk Evaluation II alone, who experienced high operative mortality. Conclusions: Model for End-stage Liver Disease score as a quantifier of hepatorenal dysfunction complements European System for Cardiac Operative Risk Evaluation II in predicting operative mortality after tricuspid valve surgery.